(untitled) (Nueva Epoca, 2025)
This text takes a closer look at how private law in Argentina has been shaped by constitutional principles and the effects this has had on consumer relationships, particularly focusing on the duty to inform. By weaving constitutional values and human rights into private law, obligations that were once seen as secondary have now become central, especially in the realm of consumer rights (as highlighted in Art. 42 of the National Constitution, Art. 4 of the Consumer Protection Law, and Art. 1100 of the Civil and Commercial Code). The duty to inform is viewed as an obligation that, due to its need for effectiveness, turns into an obligation of result (Art. 774(c) CCyCN). This means that providers are not just required to give information; they must do so in a way that is adequate, truthful, free of charge, effective, and easy for consumers to understand, even considering cases of extreme vulnerability. To make sure they meet this duty, providers need to set up both internal and external preventive systems that ensure clear information is delivered in a way that meets the consumer’s needs. In this light, information becomes a vital tool for constitutional protection, pushing providers to adopt a more preventive, transparent, and fair approach in their practices.